Body Mass Index (BMI) as an Important Factor in the Manifestation of Motor Abilities of Early Primary School Pupils - Slobodan Lj. Pavlović (University of Belgrade, Teacher Education Faculty, 2018)
The aim of this study was to determine the differences in motor skills in the lower primary school children depending on the value of the body mass index (BMI). The sample consisted of 174 students of the lower primary school grades in the city of Uzice, aged 10 ± 0.65 years. Seven motor variables were analysed to determine the quantitative differences in the areas of the motor functioning of children. The children were categorised in three groups based on the body mass index (underweight, normal weight and overweight). The results obtained in this study indicate that there are differences in the motor space among the groups of respondents. The biggest difference was identified in the speed of movement, coordination of the whole body, static strength of arms and shoulders and flexibility. A statistically less significant difference was also identified in the repetitive strength. The results suggest that children with normal nutritional status have the best motor skills, compared to the underweight and overweight children. The findings are indirectly related to the quality of physical education teaching, because students with better motor skills are more active in class in terms of movement.